2022
DOI: 10.1002/ldr.4383
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of decadal land degradation dynamics in old coal mine areas of Central India

Abstract: The present study attempts to understand land use land cover change dynamics in an area subjected to opencast and underground coal mining for the last few decades in Kotma Coalmines of Anuppur District in Madhya Pradesh, India through geospatial techniques. Land use and land cover (LULC) change detection analysis was performed digitally classifying LANDSAT-5 (2001) as well as LANDSAT-8 (2020) satellite data using a maximum likelihood algorithm. Results revealed that area under dense native vegetation decrease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 68 publications
0
6
0
Order By: Relevance
“…For non‐structural degradation, Neeraj et al (2023) reported the role of heavy metal pollution in influencing soil fertility in different locations in north India (Neeraj et al, 2023). In another study, Thakur et al (2022) use satellite data (LANDSAT‐5 and 8) to report a substantial increase in degradation of forest ecosystems due to open and closed mining activities in central India. This study showed that 15.84 km 2 area has been converted to a highly inhospitable condition in the last 20 years, which certainly have negative consequences for wildlife and human well‐being.…”
Section: Review Of Papers Published In This Issuementioning
confidence: 99%
See 2 more Smart Citations
“…For non‐structural degradation, Neeraj et al (2023) reported the role of heavy metal pollution in influencing soil fertility in different locations in north India (Neeraj et al, 2023). In another study, Thakur et al (2022) use satellite data (LANDSAT‐5 and 8) to report a substantial increase in degradation of forest ecosystems due to open and closed mining activities in central India. This study showed that 15.84 km 2 area has been converted to a highly inhospitable condition in the last 20 years, which certainly have negative consequences for wildlife and human well‐being.…”
Section: Review Of Papers Published In This Issuementioning
confidence: 99%
“…This study showed that 15.84 km 2 area has been converted to a highly inhospitable condition in the last 20 years, which certainly have negative consequences for wildlife and human well‐being. Authors used land degradation vulnerability index to report that mining activities have placed 8.60% of the tropic dry forests under high vulnerability in Annupur district in Madhya Pradesh (Thakur et al, 2022).…”
Section: Review Of Papers Published In This Issuementioning
confidence: 99%
See 1 more Smart Citation
“…While several renewable sources, like sunlight, water, wind, etc., can provide energy, they are either inherently impossible or challenging to regulate or exhibit climate dependency, which is becoming increasingly unpredictable daily. In this regard, plant biomass has once again become a viable alternative to increase the options for renewable energy sources [210][211][212].…”
Section: Prospective Resource Recovery In Constructed Wetland (Cw) Sy...mentioning
confidence: 99%
“…Large-scale mining operations are likely to exert a considerable impact, resulting in damage to surface vegetation and underground water resources, posing a substantial threat to the delicate ecological balance in the region. [5][6][7][8][9][10]. Therefore, in the current situation where the public is increasingly concerned about the living environment and the country strongly advocates ecological civilization construction, for arid and semi-arid desertified mining areas with extremely scarce water resources, solid filling materials are the most ideal choice.…”
Section: Introductionmentioning
confidence: 99%